Exploring the Experiences of Health Professionals Studying a Master of Public Health Programme Through Distance Learning at a South African University - Mwanda, Ziyanda; Gachago, Daniela; Hodgkinson-Williams, Cheryl (Commonwealth Youth and Development, 2025)
The demand for highly skilled health professionals continues to increase in low- and middle-income countries such as South Africa. Postgraduate programmes such as the Master of Public Health (MPH) programme are recognised as critical contributors to strengthening health professionals’ skills to meet healthcare demands. The MPH programme allows health professionals to study while working through distance learning platforms. However, it does not produce as many graduates as it should due to dropout rates and low throughput. This study aimed to highlight the challenges and enablers that affect postgraduate students enrolled at a traditionally contact university studying through distance learning platforms. The study employed qualitative methods, namely semi-structured interviews and a photovoice project. The study found that distance students’ challenges varied and that they drew support from both the formal and informal settings of their microsystems. The study found that in the absence of an ecosystem approach, students’ needs often go unmet at traditional contact institutions. A recommendation is made for less rigid and more fluid boundaries between settings to be established. Multistakeholder collaboration can result in meaningful connections, through shared learning and communication, which have been identified as key elements for responsive student support.